POTENSI DAUN PURING (Codiaeum variegatum) DALAM MENYERAP LOGAM TIMBAL (PB) DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Asriani Suhaenah; St. Maryam; Gusmiati Gusmiati (Fakultas Farmasi UMI, 2020)
One type of pollution that must be taken into concern is lead metal (Pb) as an element that is harmful to humans. Croton leaves contain tannin chemical compounds that able to bind lead (Pb). The research aimed to determine to potency of croton leaves as an adsorbent of lead (Pb). The research used a metal content measurement method based on the adsorption of croton leaves by atomic absorption spectrophotometry (AAS). The results showed that the absorption of lead was based on 3 gram concentrations in the samples, namely sample (1) 0.1181 gram of 1.9991 µg/g, sample (2) 0.3179 gram of 0.0871 µg/g and sample (3) 0.5117 gram of 0.2171 µg/g. in the use of parameter of the sample concentration it is indicated that at mass 0.1181 gram, the lead metal content showed a maximum absorption of 1.9991 µg/g sample.